Structural insights into integrin α(5)β(1) opening by fibronectin ligand - Schumacher, Stephanie (Sci Adv, 2021)
Integrin α(5)β(1) is a major fibronectin receptor critical for cell migration. Upon complex formation, fibronectin and α(5)β(1) undergo conformational changes. While this is key for cell-tissue connections, its mechanism is unknown. Here, we report cryo–electron microscopy structures of native human α(5)β(1) with fibronectin to 3.1-angstrom resolution, and in its resting state to 4.6-angstrom resolution. The α(5)β(1)-fibronectin complex revealed simultaneous interactions at the arginine-glycine-aspartate loop, the synergy site, and a newly identified binding site proximal to adjacent to metal ion–dependent adhesion site, inducing the translocation of helix α1 to secure integrin opening. Resting α(5)β(1) adopts an incompletely bent conformation, challenging the model of integrin sharp bending inhibiting ligand binding. Our biochemical and structural analyses showed that affinity of α(5)β(1) for fibronectin is increased with manganese ions (Mn(2+)) while adopting the half-bent conformation, indicating that ligand-binding affinity does not depend on conformation, and α(5)β(1) opening is induced by ligand-binding.